Social Media Type Matters: Investigating the Relationship Between Motivation and Online Social Network Heterogeneity. Issue 4 (1st October 2016) - Kim, Cheonsoo; Lee, Jae Kook
Abstract : This study investigated relationships between social media motivation, relative preferences for social media type, and network heterogeneity, using a U.S. national survey. By classifying social media into the symmetrical and the asymmetrical, we showed that relationship motivation was more likely to be associated with a preference for the symmetrical type, whereas information motivation with a preference for the asymmetrical. Network heterogeneity was positively predicted by relationship motivation but not by information motivation. Finally, a relative preference for the symmetrical type was found to mediate the association between relationship motivation and network heterogeneity.